2021
DOI: 10.21037/apm-21-546
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of VCAM-1, IL-6, and IL-17A in patients with allergic rhinitis

Abstract: Background: Allergic rhinitis is a chronic inflammatory disease with a high incidence, affecting the quality of life of patients. The aim of the present study was to explore the expression and clinical significance of vascular endothelial cell adhesion molecule-1 (VCAM-1), interleukin (IL)-6, and IL-17A in patients with allergic rhinitis.Methods: A total of 180 patients with allergic rhinitis, who were admitted to our hospital from March 2017 to March 2020, were enrolled as the observation group. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…Prior research has also often adopted the above indicators for observation of the pathological development of AR [ 21 , 22 ]. Similar to prior research [ 23 , 24 ], the times of sneezing and rubbing the nose, IgE, IL-4, IL-6, and HA levels in the AR group all greatly increased in our study, which can also verify the success of modelling. As everyone knows, IgE is a crucial factor that mediates allergic inflammatory diseases of the respiratory tract, which is primarily produced by plasma cells in the mucosa lamina propria of the respiratory tract and digestive tract [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Prior research has also often adopted the above indicators for observation of the pathological development of AR [ 21 , 22 ]. Similar to prior research [ 23 , 24 ], the times of sneezing and rubbing the nose, IgE, IL-4, IL-6, and HA levels in the AR group all greatly increased in our study, which can also verify the success of modelling. As everyone knows, IgE is a crucial factor that mediates allergic inflammatory diseases of the respiratory tract, which is primarily produced by plasma cells in the mucosa lamina propria of the respiratory tract and digestive tract [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…IL6 is also involved in the pathophysiology of allergic diseases, and high levels of IL-6 in the blood promote the release of allergic mediators and exacerbate allergic rhinitis [ 36 , 37 ]. In addition, it has been suggested that the allergic rhinitis symptoms are alleviated by inhibiting the higher IL-6 expression level [ 38 ], which is a result supporting the pharyngeal allergic inhibitory effect of EAT [ 2 ]. Similar to IL-6, we showed that EAT downregulates the mRNA expression of tumor necrosis factor alpha (TNFα), one of the most crucial proinflammatory cytokines, along with IL-6 ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that ICAM-1 and VCAM-1 enhance the inflammatory response and are involved in various diseases (69)(70)(71)(72). It has been well known that ICAM-1 and VCAM-1 play roles in arresting immune cells and initiating TEM, which plays an essential step in the development of atherosclerosis.…”
Section: Rt-pcr Analyses Confirmed the Expression Of Integrins Avb3mentioning
confidence: 99%